2015
DOI: 10.1007/s40725-015-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Data from Discrete Return Airborne LiDAR and Optical Sensors to Enhance the Accuracy of Forest Description: A Review

Abstract: Good forest management requires comprehensive and reliable inventory data spanning large areas. Forest management has increasingly relied on remote sensing, specifically light detection and ranging (LiDAR). However, due to the high costs associated with data collection and processing, wall-to-wall LiDAR data is rarely obtained for forests. In contrast, multispectral imagery from optical sensors often covers large extents but they fail to capture detail below the forest canopy and do not directly measure struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…Forest inventory measurements derived from ALS data are often extrapolated to regional or national scales using covariates obtained from optical or radar satellite observations [28][29][30]. This multi-sensor upscaling approach facilitates the wall-to-wall retrieval of forest inventory biometrics through the integration of wide-area satellite observations, high-resolution ALS data and field measurements acquired from a representative sample of forests [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Forest inventory measurements derived from ALS data are often extrapolated to regional or national scales using covariates obtained from optical or radar satellite observations [28][29][30]. This multi-sensor upscaling approach facilitates the wall-to-wall retrieval of forest inventory biometrics through the integration of wide-area satellite observations, high-resolution ALS data and field measurements acquired from a representative sample of forests [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2013) used a hierarchical object-based classification method to classify urban vegetation with high-resolution aerial photography alone [71] and obtained a classification accuracy of 90.5%, which indicates that the object-based classification method was effective for vegetation mapping, including for trees and grasses. Xu et al (2015) reviewed the application of fused airborne LiDAR and optical sensors in forest description [72]. The review demonstrated that the fusion of multiple remote sensing data could improve the performance of forest areas extraction (about 20% accuracy improvement).…”
Section: Performance Of Different Classification Methods For Trees and Grasses Extractionmentioning
confidence: 99%
“…Fusion of multispectral images such as Landsat ETM+ and SAR has two major advantages: (1) enhancement of spectral information; and (2) reducing the problem of cloud cover because SAR is less affected by cloud cover [119]. LiDAR was also integrated with Landsat ETM+ images in order to improve mapping of vertical and longitudinal characteristics of different land cover types [120][121][122]. Generally, when correct algorithms are applied during image fusion of Landsat images with other remote sensing data, improvements are expected on the results of land cover classification [117,123,124].…”
Section: Landsat Image Fusions In Land Cover Classificationmentioning
confidence: 99%